Dietary PlsEtn Ameliorates Colon Mucosa Inflammatory Stress and ACF in DMH‐Induced Colon Carcinogenesis Mice: Protective Role of Vinyl Ether Linkage. Issue 2 (29th September 2020) - Nguma, Ephantus; Tominaga, Yuki; Yamashita, Shinji; Otoki, Yurika; Yamamoto, Ayaka; Nakagawa, Kiyotaka; Miyazawa, Teruo; Kinoshita, Mikio
Abstract: Ethanolamine plasmalogen (PlsEtn), a sub‐class of ethanolamine glycerophospholipids (EtnGpl), is a universal phospholipid in mammalian membranes. Several researchers are interested in the relationship between colon carcinogenesis and colon PlsEtn levels. Here, we evaluated the functional role of dietary purified EtnGpl from the ascidian muscle (87.3 mol% PlsEtn in EtnGpl) and porcine liver (7.2 mol% PlsEtn in EtnGpl) in 1, 2‐dimethylhydrazine (DMH)‐induced aberrant crypt foci (ACF) in vivo, and elucidated the possible underlying mechanisms behind it. Dietary EtnGpl‐suppressed DMH‐induced aberrant crypt with one foci (AC1) and total ACF formation ( P < 0.05). ACF suppression by dietary ascidian muscle EtnGpl was higher compared with dietary porcine liver EtnGpl. Additionally, dietary EtnGpl decreased DMH‐induced oxidative damage, overproduction of TNF‐α, and expression of apoptosis‐related proteins in the colon mucosa. The effect of dietary ascidian muscle EtnGpl showed superiority compared with dietary porcine liver EtnGpl. Our results demonstrate the mechanisms by which dietary PlsEtn suppress ACF formation and apoptosis. Dietary PlsEtn attained this suppression by reducing colon inflammation and oxidative stress hence a reduction in DMH‐induced intestinal impairment. These findings provide new insights about the functional role of dietary PlsEtn during colon carcinogenesis.